The Impact Of Military Personnel Involvement in Civilian Positions in the Reform Era: A Review of The Indonesian National Armed Forces (TNI) Law - Zahra Malinda Putri; Muhammad Panca Prana Mustaqim Sinaga; Bintang Ardiansyah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
After the birth of the reform era, the political conditions of the Indonesian state experienced quite big changes, one of which was the limitation of the military's role in political practice in Indonesia. The military's role was returned to the national defense function in order to maintain the professionalism of the Indonesian National Army (INA). The involvement of active military members in civilian positions which is now starting to reappear has given rise to political and legal turmoil which indicates the emergence of dual functions of Indonesia Armed Forces(IAF) as during the New Order era. This harms the goals of reform and the meaning of democracy in Indonesia. This requires providing views on the impact of involvement of military members in civilian positions both from a legal, social and political perspective. Through a statutory regulatory approach, a historical approach, and a conceptual approach using qualitative normative research, we can analyze the impact of military members' involvement in civilian positions in a descriptive analytical manner. The existence of civil-military stability makes government administration strong and of high quality, however, legal uncertainty, weakening of democracy, and inequality in political practices will give rise to injustice and disrupt the nation's welfare.